Islam, Maqasid al-Shariah, and sustainable development: an edu-action approach - Mhd. Sarif, Suhaimi (2021)
This paper explores edu-action approach in transferring knowledge, skills, attitude and habit in sustainable development from Islamic perspective. Firstly, the paper explores the edu-action in the philosophy of Islam on sustainable development from relationships and connections. Secondly, the paper examines the nature of Islamic development. Thirdly, the paper explains the roles of individuals, groups, society and economy on sustainable development. Then, the paper investigates sustainable development in local, national, regional and global levels. Remarkable, the paper explores the application of maqasid al-shariah into sustainable development. The essence of the paper is about applying Islamic sustainable development in practices.